Sistem Inventarisasi Barang Dinas Pendidikan Nasional Kuningan Jawa Barat - Neneng Nuryati; Carolina Magdalena Lasambouw; Djoni Djatnika; Lina Meilinda; Muhammad Rizqi Sholahuddin; Setiadi Rachmat; Maisevli Harika (JURIKOM (Jurnal Riset Komputer), 2021)
The national education department's inventory record is unique because the goods are in schools under service, not in the office. Inventory complexity has increased due to the procurement of different schedules and reports, not only for internal but also for other institutions concerned. A structured and accessible inventory from anywhere is the right choice for the effectiveness and efficiency of this work. This research aims to design a website-based information system for goods inventory in the National Education Office (DISDIKNAS). The software development method used in this study is the Rational Unified Process. The study results obtained a web-based application that can help DISDIKNAS inventory goods in a structured and accessible anywhere